Overexpression of AKR1B10 Predicts Poor Prognosis in Gastric Cancer Patients Undergoing Surgical Resection - Yu-Yin Liu; Yueh-Wei Liu; Gong-Kai Huang; Kuo-Chen Hung; Yu-Hung Lin; Cheng-Hsi Yeh; Shih-Min Yin; Ching-Hua Tsai; Yen-Hao Chen (Current Oncology, 2022)
Aldo–keto reductase family 1 member B10 (AKR1B10) is associated with several cancers, but the prognostic role in gastric cancer (GC) remains unclear. We enrolled 359 GC patients who underwent a gastrectomy with D2 lymph node dissection. AKR1B10 expression was scored using an immunoreactive scoring system based on immunohistochemistry. Adjuvant chemotherapy with S-1 or oxaliplatin plus capecitabine was administered to pathological stage II or III disease patients. There were 117 (32.6%) and 242 (67.4%) patients with AKR1B10 overexpression and low expression, respectively. Patients overexpressing AKR1B10 had worse 5-year disease-free survival (DFS) and overall survival (OS) rates than those with low expression of AKR1B10. Pathological T3–T4 stage, pathological stage III, lymph node ratio ≥25%, and AKR1B10 overexpression were independent prognostic factors for worse DFS and OS in univariate and multivariate analyses. For 162 stage II or III patients who received adjuvant chemotherapy after surgical resection and 59 patients with signet ring cell carcinoma histology, AKR1B10 overexpression was also associated with inferior DFS and OS. AKR1B10 was not associated with clinical survival in stage I GC patients. In conclusion, AKR1B10 overexpression may be an independent prognostic factor for worse survival in GC patients who underwent gastrectomy with D2 lymph node dissection.